Phonetic features of the vernacular of the Russian language (Based on the novel by Saltykov-Shchedrin "The History of a City") - Burkhanov Abduvali Abdullayevich (Zien Journals, 2022)
The article discusses the issues of the organic inclusion of new technologies in the educational process, the developed and substantiated technologies for the use of innovative forms of education in the study of the phonetic features of the vernacular of the Russian language.
Keywords: Steele Shchedrin; semantics; ambiguity; work